Manufacturer’s Collaborative Business Strategy with Two Different Reverse Channels in a Closed-Loop Supply Chain - Sungwook Yoon; Sukjae Jeong (Complexity)
Reuse of products has become increasingly critical to reduce manufacturing costs and revitalize the new product market. With two different investment perspectives, manufacturers cooperate with retailers and recyclers to collect products from customers. By investing in the retailer, manufacturers gain an opportunity to sell new products, whereas by investing in the recycler, manufacturers can reduce production costs through remanufacturing. Therefore, manufacturers must determine the appropriate investment strategies to be applied to the two channels by analyzing the trade-offs between these opportunities. For this purpose, we discuss three investment strategies: Revenue-Sharing Investment, Direct Subsidy per Unit Returned Cartridge, and Hybrid Investment. The system dynamics model is used to construct scenarios of various investment strategies used by the manufacturer with the collection partners and analyze the corresponding changes in the revenues of the manufacturer. The results indicate that the application of the revenue-sharing strategy and the hybrid strategy to support retailers and recyclers is effective in increasing manufacturer profit. More specifically, by considering the hybrid investment strategy of revenue-sharing investment and the direct subsidy per unit returned cartridge for the recycler, the manufacturer can simultaneously avoid excess investment by the recycler and promote return activities through the recycler.